ONLINE REPUTATION CONCEPTUALIZATION - Shiddiq Sugiono (Mediakom, 2020)
The development of information and communication technology is considered to have expanded the concept of reputation in the online realm. This expansion has an urgency for further investigation because in this case the internet has become the main medium used to find various sources of information. The purpose of this study is to further conceptualize online reputation and map the variables that become the impact of this concept based on studies from various academic literature. This article is a literature study using systematic literature review techniques through a qualitative approach. Basically, online reputation is rooted in the concept of word of mouth, this is consistent with the organizational reputation management model that has been formulated previously. The availability of various information on the internet becomes a source for someone to determine the reputation of an object. Online reputation must be followed by management efforts so that the expected results of the online activity strategy can be obtained. The variables that are the impact of online reputation management include: verification of asymmetric information, building personal and product brands, building brand loyalty, building trust in conducting online transactions.